Computational Design of a Truncated Javan Spitting Cobra (Naja sputatrix) Venom Cardiotoxin Analogue as a Promising Insulinotropic Agent - Dinana, Ichda Arini; Widodo, Widodo; Kurniawan, Nia (Universitas Brawijaya, 2023)
Treatment options for diabetes may vary widely, however, around 50% of all diabetic patients do not reach the minimum glycemic target. Therefore, drugs that are able to lower glucose levels through unconventional targets are still needed for the treatment of type 2 diabetes. This study aimed to investigate the activity of cardiotoxins from Naja sputatrix towards Kv channels as potential targets for glucose level reduction. Molecular docking analysis was conducted using the ClusPro web server, and the resulting protein-ligand interactions were visualized using BioVia Discovery Studio and LigPlus v.4.5.3. The stability of the docking structures was further examined through molecular dynamics simulations. The CTX-1, CTX-3, CTX-4, CTX-5, and CTX-KJC3 sequences from N. sputatrix were aligned and modeled, focusing on the 62-81 amino acid residues. The CTX-3, CTX-4, and CTX-5 models demonstrated interactions with the binding site of the KcsA receptor. Additionally, substituting the Val73 residue in the CTX62-81 fragment with Lys73 resulted in reduced binding energy and mitigated the cytotoxic effects of CTX while maintaining its insulinotropic activity.